CARBON PASTE ELECTRODE HEXADECYLTRIMETHYLAMMONIUM BROMIDE MODIFIED NATURAL ZEOLITE FOR CHROMIUM(VI) DETECTION - Budi Riza Putra; Latifah K Darusman; Eti Rohaeti (Universitas Gadjah Mada, 2013)
A simple voltammetric technique for quantification of chromium(VI) is presented in this work. The technique is based on linear sweep voltammetric reduction Cr(VI) on hexadecyltrimethylammonium bromide (HDTMABr) modified Lampung zeolite carbon paste electrode. Selected HDTMABr concentration for natural zeolite modification is obtained 200 mM. Working electrode for chromium(VI) detection is made by graphite, paraffin oil and HDTMABr modified Lampung zeolite. The effect of supporting electrolyte matrix, pH and also scan rate is also investigated. The calibration curve for chromium(VI) detection using the proposed method shows linearity from 0.2 to 1.0 mM with sensitivity, detection and quantification limit, and precision was 0.4294 mM, 3.63 x 10-4 mM, 1.197 x 10-3 mM, 4.49%, respectively.